2017
DOI: 10.3390/molecules22030459
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Anti-Mitotic Activities and Other Bioactivities of Sesquiterpene Compounds upon Human Cells

Abstract: We review the bio-activities of natural product sesquiterpenes and present the first description of their effects upon mitosis. This type of biological effect upon cells is unexpected because sesquiterpenes are believed to inactivate proteins through Michael-type additions that cause non-specific cytotoxicity. Yet, certain types of sesquiterpenes can arrest cells in mitosis as measured by cell biology, biochemical and imaging techniques. We have listed the sesquiterpenes that arrest cells in mitosis and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 122 publications
(188 reference statements)
2
26
0
Order By: Relevance
“…Additionally, we have previously shown that C. minima ethanol extract (CME) could inhibit the proliferation of CNE-1 cells and activation of the PI3K–AKT–mTOR signaling pathway (Guo et al, 2015). Brevilin A is a single compound belonging to the SQL class of chemicals isolated from C. minima , with a variety of pharmacological activities (Liu et al, 2005; Chan et al, 2016; Bosco and Golsteyn, 2017). Previous studies have demonstrated the anti-cancer activity of SQLs isolated from C. minima in various cancers, including colon cancer (Huang et al, 2014), prostate cancer (Vishwanath Pradeep et al, 2012), and NPC (Su et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we have previously shown that C. minima ethanol extract (CME) could inhibit the proliferation of CNE-1 cells and activation of the PI3K–AKT–mTOR signaling pathway (Guo et al, 2015). Brevilin A is a single compound belonging to the SQL class of chemicals isolated from C. minima , with a variety of pharmacological activities (Liu et al, 2005; Chan et al, 2016; Bosco and Golsteyn, 2017). Previous studies have demonstrated the anti-cancer activity of SQLs isolated from C. minima in various cancers, including colon cancer (Huang et al, 2014), prostate cancer (Vishwanath Pradeep et al, 2012), and NPC (Su et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Brevilin A is a sesquiterpene lactone isolated from CM, and possesses a variety of pharmacological activities [13,14,36]. Arnicolide C and arnicolide D are also sesquiterpene lactones isolated from CM [1,12,13,32,33], however, relatively few studies have been conducted to investigate their biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…It phosphorylates and activates cell division cycle 25 (CDC25) to foster the exit from mitosis through activation of anaphase-promoting complex/cyclosome (APC/C) and the proteolytic machinery 4 . PLK1 is attached to the mitotic spindles through different stages of cell division 5 , which stabilizes the kinetochore–microtubule attachment and triggers the transition from meta- to anaphase 6 . PLK1 overexpression correlated with tumor progression and poor prognosis in different cancer types7., 8..…”
Section: Introductionmentioning
confidence: 99%